Biochar can Increase Chinese Cabbage (Brassica oleracea L.) Yield, Decrease Nitrogen and Phosphorus Leaching Losses in Intensive Vegetable Soil - Sun H; Jeyakumar P; Xiao H; Li X; Liu J; Yu M; Rana P; Shi W (Tech Science Press)
There are few evidences on the effect of biochar on vegetable yield, nitrogen (N) and phosphorus (P) leaching losses under intensive vegetable production soil. The current field plot scale study evaluated responses of Chinese cabbage (Brassica oleracea L.) yield, N and P leaching losses using five N treatments of common N application rate according to local farmers’ practice (N100%), reducing 20% or 40% N fertilizer (N80% and N60%), and reducing 40% N fertilizer but incorporating 10 or 20 t/ha biochar (N60% + BC10 and N60% + BC20). Results showed that N80% and N60% decreased both the cabbage economic and leaf yields by 6.8%–36.3% and 27.4%–37.7%, respectively. Incorporation of biochar with reduced N fertilizer rates improved the cabbage yield, in particular the N60% + BC20 matched the yield that observed in N100% treatment. Enhanced N and P uptake capacities of cabbage shoot probably contributed the higher vegetable production under both biochar amendment schemes. Biochar application mitigated the NH+4-N and total P leaching losses by 20%–30% and 29%–32%, respectively, compared with their counterpart treatment N60%. Nevertheless, biochar exerted no influence on the NO–3-N leaching. In addition, soil organic matter content was recorded with 7.4%–28.7% higher following 10–20 t/ha bio-char application. In conclusion, biochar application can increase economic yield of cabbage via increasing N and P use efficiency, decrease N and P leaching losses, and improve soil quality in an intensive vegetable production system.
Keywords: Biochar; leachate; non-point source pollution; vegetable yield; soil quality